Antecedents of Leadership and Work Culture on Employee Work Discipline - Syah, Amirul; Alzen, Alzen (AIBPM Publisher, 2023)
The purpose of this study was to determine, to know and to analyze the influence of leadership on work discipline at PT. Nusantara Plantation III (Persero) Medan. The approach used is an associative approach. The population in this study are all employees of PT. Perkebunan Nusantara III (Persero) Medan. Data collection techniques using a questionnaire. Data analysis techniques used the Classical Assumption Test, Multiple Regression, t-test and F-test, and the coefficient of determination. Data processing used the SPSS software program (version 24.00). Partially it is known that leadership and work culture have a positive and significant influence on work discipline performance. Simultaneously it is known that leadership and work culture have a significant positive influence on work discipline at PT. Nusantara Plantation III (Persero) Medan. Simultaneously it is known that leadership and work culture have a significant positive influence on work discipline at PT. Nusantara Plantation III (Persero) Medan.